Relações de trabalho no semiárido: um olhar a partir das ações de convivência com o semiárido desenvolvidas pelo CEDASB no sudoeste baiano - Silva, Leandra Pereira da (2023)
The main objective of this dissertation is to analyze the contribution of actions of coexistence with the semi-arid in the modification of labor relations in the semiarid region, specifically, of women and men who are beneficiaries of the projects carried out by CEDASB in the community of Bomba, municipality of Belo Campo – Ba. To investigate the core of the issue, we focus on the main public policies directed to workers in the semiarid region, analyzing how this territory was perceived within the scope of such policies. This work had as methodological basis the approach of qualitative research and militant research. The methodological procedures used were based on: bibliographic research; documentary research; fieldwork with the application of interviews, conversation circles, photographic records and observation. In the results, it is observed that CEDASB has been consolidated as a CSO with political and technical capital capable of developing a series of actions and projects in the State of Bahia. Specifically in the community investigated, the public policies of coexistence with the Semiarid impacted on the lives of workers in the form of generation of monetary and non-monetary income, although the income of families is considered low, improvement in the quality of life of families not only because they have access to quality water, but because they participate in a whole pedagogical action that has debated elements related to territoriality, the diversification of production, Food and Nutrition Security and Sovereignty, and the work of women in caring for life in the territory.